HLA in Colombia Wayu from Guajira Peninsula Amerindians: Pacific Ocean relationships. (2019)
Wayu Amerindians live around Guajira Peninsula shared by Colombia and Venezuela. Wayu from Colombia have been studied for their HLA profile and these data put in context with both genetic and cultural relatedness to Pacific Islanders. HLA-A*24 and HLA-B*35 (most likely HLA-A*24:02 and HLA-B*35:05) and HLA-DRB1*04:03 and HLA-DQB1*03:02 are shared both by Wayu and other Amerindians and Pacific Islanders in specific high frequency. Our findings further suggest a genetic relationship between Amerindians (also Wiwa/Arsario and Chimila from Colombia; Uros from Peru) and Pacific Islanders. Titikaka Lake (Peru/Bolivia) Amerindians (Aymara, Uros and Quechua) share also cultural traits, like Tiwanaku (Titikaka Culture giant statues) and Easter Island Culture giant statues or “Moais”. © 2018